2018
DOI: 10.1111/ldrp.12183
|View full text |Cite
|
Sign up to set email alerts
|

Examining IEPs of English Learners with Learning Disabilities for Cultural and Linguistic Responsiveness

Abstract: Effective education of English learners (ELs) with learning disabilities requires special educators to deliver culturally/linguistically responsive instruction within the context of special services, embracing the interaction between exceptionality and diversity. A critical concept is the notion that cultural and linguistic features are mandated by law to remain integral to teaching and learning once ELs are appropriately placed for special services. We examined a sampling of IEPs for ELs receiving special edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The IEP is the cornerstone of a quality education for EBs. Yet, IEPs contain little or no reference to students' diverse linguistic and cultural characteristics and do not recommend native language or English as a second language instruction or accommodations that should be provided to EBs (Hoover, Erickson, Patton, Sacco, & Tran, 2018). Without such guidance, instruction will reflect educators' perceptions and beliefs, not evidence-based practices.…”
Section: Individualized Education Programsmentioning
confidence: 99%
“…The IEP is the cornerstone of a quality education for EBs. Yet, IEPs contain little or no reference to students' diverse linguistic and cultural characteristics and do not recommend native language or English as a second language instruction or accommodations that should be provided to EBs (Hoover, Erickson, Patton, Sacco, & Tran, 2018). Without such guidance, instruction will reflect educators' perceptions and beliefs, not evidence-based practices.…”
Section: Individualized Education Programsmentioning
confidence: 99%
“…Studies conducted after the reauthorization of the 2004 IDEA suggest that the issue of congruence among identified needs, goals, and services delivered remains a concern (see Catone & Brady, 2005; Hoover et al., 2019; Hott et al., 2019). In addition, the types and settings of service offerings may not be individualized (Kurth et al., 2019a, Kurth et al., 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Hoover et al. (2019) examined 30 IEPs of elementary and secondary students with SLD who were also English Language Learners (ELLs). They found the IEPs did not contain goals related to ELL needs, and did not contain evidence‐aligned accommodations to help ELLs with SLD access the general education curriculum.…”
Section: Previous Iep Reviewsmentioning
confidence: 99%
“…Unfortunately, very little attention has been dedicated to the development of CLR IEPs and very little research has been directed at examining this topic. For example, in their pilot project review of literature, (Hoover, Erickson, Patton, Sacco, & Tran, 2018) found few studies that directly addressed IEPs for diverse learners. Through their pilot project, they examined 29 IEPs of ELs classified as having a learning disability in two school districts.…”
mentioning
confidence: 99%
“…The most notable finding was that almost none of the IEPs contained CLR features to inform teachers on how to best educate culturally and linguistically diverse students with a learning disability, thus jeopardizing the provision of an appropriate education. Specifically, “IEPs clearly lack attention to cultural and linguistic diverse features, qualities, and strengths that teachers must understand to provide ELs with a learning disability effective special education” (Hoover et al, in press).…”
mentioning
confidence: 99%